Enamel Carious Lesion Development in Response to Sucrose and Fluoride Concentrations and to Time of Biofilm Formation: An Artificial-Mouth Study. (15th September 2014) - Arthur, Rodrigo Alex; Kohara, Eduardo Kazuo; Waeiss, Robert Aaron; Eckert, George J.; Zero, Domenick; Ando, Masatoshi
Abstract : The aim of this study was to evaluate both sucrose and fluoride concentrations and time of biofilm formation on enamel carious lesions induced by an in vitro artificial-mouth caries model. For Study 1, biofilms formed by streptococci and lactobacilli were grown on the surface of human enamel slabs and exposed to artificial saliva containing 0.50 or 0.75 ppmF (22.5 h/d) and broth containing 3 or 5% sucrose (30 min; 3x/d) over 5 d. In Study 2, biofilms were grown in the presence of 0.75 ppmF and 3% sucrose over 3 and 9 days. Counts of viable cells on biofilms, lesion depth (LD), and the integrated mineral loss (IML) on enamel specimens were assessed at the end of the tested conditions. Counts of total viable cells and L. casei were affected by sucrose and fluoride concentrations as well as by time of biofilm formation. Enamel carious lesions were shallower and IML was lower in the presence of 0.75 ppmF than in the presence of 0.50 ppmF( P < 0.005 ) . No significant effect of sucrose concentrations was found with respect to LD and IML( P > 0.25 ) . Additionally, deeper lesions and higher IML were found after 9 d of biofilm formation( P < 0.005 ) . Distinct sucrose concentrations did not affect enamel carious lesion development. The severity of enamel demineralization was reduced by the presence of the higher fluoride concentration. Additionally, an increase in the time of biofilm formation produced greater demineralization. Our results also suggest that the present model is suitable for studying aspects related to caries lesion development.